RESEARCH OF WHEEL-RAIL WEAR DUE TO NON-SYMMETRICAL LOADING OF A FLAT CAR - Shatunov, O. V.; Shvets, A. O.; Kirilchuk, O. A.; Shvets, A. O. (Science and Transport Progress, 2019)
Purpose. The paper is aimed at determining the influence of non-symmetrical loading of a flat car on the magnitude of the wear factor of a wheel-rail pair when changing the operation parameters that occur in operation. Methodology. The dynamic loading of the flat car, model 13-401 with typical three-piece bogies is studied using a model of spatial oscillations of a five-car coupling with the help of mathematical and computer simulation. Theoretical calculations are performed for the most dangerous sections of the railway track – small and medium radius curves in the range of permissible speeds. Findings. The indicators of wear of the rolling stock wheels and the rails are analysed on the example of flat cars in the presence of a longitudinal and transverse displacement of the load mass centre relative to the car symmetry centre. To obtain information on the effect of permissible deviations of the arrangement of cargo in the car on the magnitude of the dynamic loading of the wheel-rail contact, the authors performed theoretical studies of the spatial variations of the rail carriage and its interaction with the track. Originality. To determine the wear of the wheel-rail pair, the effect of displacement in two directions from the central axis of symmetry of the load gravity centre was studied, taking into account the value of the travel speed along the curved sections of the small and medium radius using a mathematical model of coupling of five freight cars. Practical value. As a result of the theoretical studies carried out, the authors assessed such factors as wear factor, directional force, and hunting of the wheel set of freight rolling stock in the event of load gravity centre displacement when moving along curved sections of the railway track. To establish the possible cause of intensive wear of the wheels and rails, the following parameters were analysed: lozenging of front bogie side frames; hunting of the left side frame of the front bogie; mutual longitudinal movement of the side frame and axle box of the front wheel set; mutual hunting of the left side frame of the bogie relative to the front wheel set.